Rancang Bangun Sistem Kontrol Peralihan Beban pada Dua Generator Set Secara Automatis - Ridwan Baharta; Winarto Winarto; Nurjan Didik (Jurusan Teknologi Pertanian, 2014)
This research is the development of a generator that can be on/off automatically based on the existence of commercial power. Genset used in the study is the generator of household scale premium gasoline. In particular, this study aims to make switching system for two generators with timer settings to prevent loss of power. Testing the performance of the system is made to ensure that the system is functioning properly. Specification design tool created an amalgamation of two generators which can perform on/off according to a predetermined time. After the generator 1 operating for 4 hours, then automatically generator set 2 will live. About 10 seconds since the first 2 live generator, the generator 1 is still in operation, then the load will be transferred to the generator 2. With this delay system, then nothing happens lost power. This mechanism will be repeated after 4 hours of generator 2 operates. With this system, the availability of electrical power would continue as needed.Â Keywords: automatic transfer switch, generator set